Defining and Managing Pain in Stroke and Traumatic Brain Injury Research - Larson, Christina M (Comp Med, 2019)
Neurologic conditions such as stroke and traumatic brain injury are challenging conditions to study in humans. Animal models are necessary to uncover disease processes and develop novel therapies. When attempting to model these or other neurologic diseases, the accompanying anesthesia and analgesia create variables that are not part of the onset of the clinical disease in the human population but are critical components of the postinjury care both in humans and animals. To maximize model validity, researchers must consider whether the disease process or a novel therapy is being studied. Damage to the neurons of the brain or the spinal cord is not painful at the neural tissue itself, but alterations to nociceptive signaling along the pain pathway can induce chronic pain. In addition, trauma or surgery leading to the event is associated with damage to peripheral tissue. Inflammation is inextricably associated with tissue injury. Inflammation is known to evoke nociception in the periphery and drive long-term changes to neurons in the CNS. Analgesics and anesthetics alter these responses yet are required as part of humane animal care. Careful planning for effective drug administration consistent with the standard of care for humans and equivalent animal care is required.